Patient Blood Management – from local initiatives to European collaborations. (27th September 2017) - Bruun, M. T.; Georgsen, J.; Titlestad, K.; Yazer, M.; Murphy, M. F.
Abstract : Patient blood management (PBM), as defined by the WHO, is a patient‐focused, evidence‐based and systematic approach to optimize the management of patient and transfusion of blood products for quality and effective patient care. It is designed to improve patient outcomes through the safe and rational use of blood and blood products and by minimizing unnecessary exposure to blood products. Important elements of PBM are optimizing haemoglobin concentrations without blood transfusion, minimizing blood loss and managing anaemia, especially by use of evidence‐based transfusion guidelines and pharmacological agents. Local PBM initiatives differ substantially. In one region of Denmark, the majority of PBM initiatives over the last 10 years have been based on provider education and enforcement of national guidelines. Evaluation of the effect of these initiatives indicated that education alone can be an effective and durable method of reducing unnecessary transfusions. To improve implementation and knowledge of PBM, benchmarking of experiences between hospitals and countries seems rational, and several initiatives regarding PBM are being undertaken in Europe. Patient Blood Management in Europe (PaBloE) is a working group of the European Blood Alliance. Its objectives are to derive good practices in PBM and to develop ways to implement these practices. Within this group, several surveys have been performed relating to blood product consumption, implementation of PBM, and knowledge of PBM principles and practices among clinicians. These surveys have shown variation in transfusion rates between the participating hospitals, and variable implementation of PBM activities and monitoring of transfusion practice.